Foreign Bodies (ANU Press, 2023)
From the 18th century, Oceania became the principal laboratory of raciology for scholars, voyagers, and colonisers alike. By juxtaposing encounters and theory, this magisterial book explores the semantics of human difference in all its emotional, intellectual, religious, and practical dimensions. The argument developed is subtle, engrossing, and gives the paradigm of 'race' its full use value. Foreign Bodies is a model of analysis and erudition from which historians of science and everyone interested in intercultural relations will greatly profit. Claude Blanckaert, CNRS (Centre Alexandre Koyré), Paris, and Honorary President, French Society for the History of the Science of Man